Badania nad bonitacją drzewostanów w świetle literatury - Kędziora, Wojciech; Borecki, Tomasz; Tomusiak, Robert (Leśne Prace Badawcze, 2020)
The purpose of this paper was to review literature covering the topic of site index with particular emphasis on Scots pine, the most important forest-forming species in Poland. We discuss the history of the site index, research on various tree species, statistical modelling methods, the spatial application of site index and age impact assessment. The history of research on the site index of forest species is long and dates back to the 18th century. Many researchers thought that determining the quality of the habitat is very important from the point of view of rational forest management. The site index, as a measure of the potential of the habitat on which the forest grows, is one of the most important characteristics of forest stands. The site index depends on the selected model, but is most often expressed as the average or top height of trees of a given species at a certain age. In our review, we point out several insufficiencies of studies on the site index, external influences and the connection of the site index with spatial conditions. Furthermore, research conducted so far has not explicitly confirmed that there is a relationship between the site index of pine stands and their geographical location in Poland. More research on the site index, especially in regard with climate change, is needed.